Blended Science-Mathematics Learning in Elementary Schools: A Factor Analysis - Arifin, M Zainal; Makmuri, Makmuri; Heliawati, Leny; Zulnaidi, Hutkemri; Herlina, Eka (UIN Fatmawati Sukarno Bengkulu, 2024)
Although a great deal of study has been done on blended learning, less has been done to examine the execution component. The goal of this study is to develop a fit model and investigate the factors influencing the implementation of mixed learning in arithmetic. Stacey and Gerbic provide an effective implementation of mixed learning that takes into account four important factors: the condition of the foundation, teachers, students, and academic reflections. The method of inquiry that is employed is a quantitative overview approach. Testing utilizing arbitrary group evaluating adding up to 165 educators of grade schools in Bogor City, West Java, Indonesia, beginning from January to July 2020. The techniques used for data analysis are structural equation modeling (SEM) and descriptive analysis. The two phases of this model's evaluation are the measurement model and the structural measurement. The outcomes demonstrated that the most crucial element in improving the blended learning implementation was the teacher's state. The student's condition was the second most important factor, followed by pedagogical considerations and the state of the institution. This examination means quite a bit to use as a kind of perspective for the public authority and partners of every establishment in the progress of reinforcing the variables of executing numerical mixed learning.